Impact of the Variable Killer Ig-Like Receptor–Human Leukocyte Antigen Interactions on Natural Killer Cell Cytotoxicity Toward Foreign CD4 T Cells - Hens, Jef; Goovaerts, Odin; Ceulemans, Ann; Jennes, Wim; Kestens, Luc (Frontiers in Immunology, 2018)
Background Natural killer (NK) cells are known to mount a response against foreign target cells, where the absence of the dominant inhibitory killer Ig-like receptor (KIR)–human leukocyte antigen (HLA) interaction immensely lowers the threshold for NK cell activation. NK cells could thus constitute a vital part in the mucosal defense against cell-associated sexually transmitted diseases. Here, we performed a detailed analysis of hitherto unexplored KIR–HLA-incompatible NK cell interactions. Methods and findings In vitro, healthy NK cells were cocultured with CD4+ T cells derived from human immunodeficiency virus-1 patients, and the KIR-specific NK cell cytotoxicity was measured using flow cytometry. Genotyping of KIR and HLA predicted the KIR–HLA interactions occurring during these 124 allogeneic encounters. KIR2DL1+ NK cells were seen as the strongest intrinsic responders in the absence of their ligand with a 3.2-fold increase in KIR2DL1+ NK cells in the total NK cell response. An association between the size of the alloreactive NK cell population and the amount of CD4+ T cell death (p = 0.0023) and NK cell degranulation (p = 0.0036) was only present in NK cell donors with an activating KIR haplotype. Conclusion We demonstrate differences in the activating effect of KIR–HLA incompatibility according to the KIR involved, with KIR2DL1 as the strongest responder. An activating KIR haplotype optimized the contribution of KIR–HLA-incompatible NK cells in the total NK cell response.